Effect of Direct Fed Microbials on Body Weight, Nutreint Intake and Nutrient Digestibility in Sheep - Dangi, Rahul K.; Shekh, Makbul A.; Modi, Rakesh J.; Patel, Ashish C.; Agravat, Priyam H.; Rathod, Sunil V. (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted during mid May to July, 2023 (70 days) at Animal Nutrition Research Station, College of Veterinary Science and Animal Husbandry, Kamdhenu University, Anand, Gujarat (388001), India to investigate the effect of direct fed microbials on nutrient intake and digestibility in adult Sheep. Twenty adult sheep, which were apparently healthy, of nearly the same body weight were used. The experiment was conducted in two phases: in-vitro study to decide the level of DFM and in-vivo study. The results of in vitro study showed, significantly (p<0.05) higher IVDMD (49.55%) at 2% level of DFM. Thus, an additional in-vivo investigation was carried out at the 2% DFM level on DM basis. The sheep were allotted into two equal groups, both groups T1 and T2 were fed compound concentrate mixture and roughage in conventional farm feeding, additionally treatment group (T2) was supplemented with 2% DFM. During experimental period the animals were weighed at biweekly interval. The weight gain was not differed significantly in both the groups. The average daily DMI of experimental animals was significantly lower in T2 as compared to T1 group, respectively. The study revealed no adverse effect of DFM on dry matter and other nutrient intakes. The digestion trial was conducted on all the twenty experimental sheep once during the experimental period. The digestibility coefficient (%) of crude protein was significantly higher in treatment group T2 as compared to control T1 group. Digestibility of DM, OM, EE, CF, ADF, NDF and hemicellulose was not affected by 2% of DFM supplementation in feed over the control diet.